HUBUNGAN DIAMETER FOLIKEL DE GRAAF TERHADAP SUHU BADAN SAAT SIKLUS ESTRUS PADA SAPI BRAHMAN - Oktora Dwi Putranti; Langgeng Priyanto; Bayu Utomo (Universitas Khairun, 2023)
Success in achieving pregnancy in cows can be done with the right lust detection. Measurement of the Graaf's follicle greatly determines the estrus cycle in cattle. Precise heat detection can be done by measuring body temperature in cattle. Measurement of body temperature can be done as a way to detect estrus in cows. The purpose of this study was to determine the relationship between the diameter of the Graaf follicle and body temperature during the estrus cycle in Brahman cattle. Data collection was carried out by observing the diameter of de Graaf follicles using ultrasound, the duration of estrus, body temperature in Brahman cattle which is done every day. The data obtained will be analyzed descriptively and presented in graphical form then the data from ultrasound observations on the diameter of the de Graaf follicle will be presented in tabular form. Based on the results of research on farms at BPTU-HPT Sembawa, it was shown that the size of the Graaf follicles of Brahman cattle during estrus was 29 mm. Body temperature during estrus were 39.3℃. Based on the results of the study it can be concluded that Brahman cows during estrus experience an increase in body temperature. An increase in body temperature is also followed by an increase in the size of the Graafian follicle. The increase in body temperature is caused by an increase in estrogen levels, which is indicated by an increase in the size of the Graaf follicles during estrus. The high hormone estrogen causes an increase in blood flow body temperature to rise. Keywords: De graaf follicles, Estrus, Body Temperature.